The OÆSE endstation at BESSY II: operando X-ray absorption spectroscopy for energy materials - Garcia-Diez, Raul; Frisch, Johannes; Van Der Merwe, Marianne; Wibowo, Romualdus Enggar; Gorgoi, Mihaela; Kataev, Elmar; Jimenez, Catalina E.; Arce, Mauricio D.; Smith, William; Quevedo-Garzon, Wilson; Wilks, Regan G.; Wallacher, Dirk; et al. (Journal of Synchrotron Radiation, 2025)
The investigation of a wide range of energy materials under relevant operation conditions, allowing for real-time investigations of the (electro)chemical mechanisms governing the performance of related applications, is enabled by the new Operando Absorption and Emission Spectroscopy at EMIL (OÆSE) endstation in the Energy Materials In-situ Laboratory Berlin (EMIL) at the BESSY II synchrotron facility in Berlin, Germany. Currently primarily used for X-ray absorption spectroscopy (XAS) studies, the OÆSE endstation utilizes the undulator-based two-colour EMIL beamline (covering an energy range between 80 and 10000 eV) to enable soft, tender, and hard XAS. In this work, the setup, along with operando sample environments tailored to address specific questions, is described, emphasizing its modularity and adaptability, and detailing specific strategies to minimize undesired radiation-induced effects caused by the high brilliance of the EMIL beamline. The in situ growth of electrodeposited copper monitored by soft and hard XAS, at the Cu L3 edge (sXAS) and Cu K edge (hXAS), respectively, is used as a proof-of-concept experiment, showcasing the capabilities of the OÆSE endstation as a versatile tool for comprehensive in situ/operando studies of energy materials under relevant conditions.
CRIS-Team Scopus Importer:2025-05-30
Keywords: batteries; electrochemistry; endstation; in situ studies; operando studies; X-ray absorption spectroscopy